Variations in anesthetic requirements with body mass index in patients undergoing trans vaginal oocyte retrieval - Saxena, Dipti; Arya, Bipin; Dixit, Atul; Sanwatsarkar, Sadhna; Bhandari, Shilpa; Agrawal, Pallavi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Various techniques have been described for ultrasound guided trans-vaginal oocyte retrieval (TVOR). No single technique has been found to be superior to others. In many centers, paracervical block (PCB) is used, either alone or in conjunction with sedation for pain relief during TVOR. This aim of this study is to evaluate the variations in anaesthetic requirements with body mass index (BMI) in patients undergoing transvaginal oocyte retrieval (TVOR). Methods: This study comprised of 70 women aged between 20 to 40 years. All patients were classified according to WHO classification into four groups on the basis of their BMI. Parameters like effectiveness of paracervical block (PCB), requirement of additional anesthetic drug (propofol), time required for surgery and numbers of oocytes retrieved were studied for each group. The correlation of all these parameters with BMI was noted and statistically evaluated. Results: PCB alone was not sufficient and all patients required additional propofol for successfully completing the procedure. The requirement of propofol increased with increase in BMI of the patients. The amount of rescue propofol required in patients with BMI>30 was significantly higher as compared to females with BMI<30, irrespective of the time taken during the procedure or the oocyte retrieved. A positive correlation was also observed between number of oocyte retrieved and time taken for surgery. Conclusions: PCB is quite useful in patients with normal BMI, but it proved to be totally ineffective in obese patients (BMI>30) undergoing TVOR. The requirement of additional propofol and time taken to successfully conduct the procedure is significantly high in patients with high BMI. These alterations in anesthetic parameters with change in BMI have vital implications and they should be taken into consideration while managing obese patients undergoing TVOR.